The Impact of Return on Risk Asset, Net Profit Margin, Earnings Per Share, and Inflation on Digital Banks’ Stock Prices (2020–2023) - Arumdani, Mirmaningtyas Sekar; Winarni; Septian Yudha Kusuma (Universitas Pamulang, 2025)
This study aims to identify and analyze the effect of return on risk assets (RORA), Net Profit Margin (NPM), earnings per share (EPS), and inflation on stock prices at digital bank for the 2020-2023 period. This research employed a causal quantitative research design. The research population consisted of digital banks listed on the Indonesia Stock Exchange (IDX). A purposive sampling technique was used, resulting in a sample of five digital banks. The study observes quarterly data from Q2 2020 to Q4 2023, producing 75 observations (15 quarterly financial reports from each of the five banks). Secondary data were obtained from financial reports available on the official IDX website (www.idx.co.id) and the official websites of each of the digital banks. Inflation data were sourced from the official website of Bank Indonesia (www.bi.go.id). The data analysis method used in this study was multiple linear regression analysis. The analysis techniques include the F-statistic test, t-statistic test, and coefficient of determination test. The results indicate that RORA and EPS have a positive and meaningful effect on stock prices, NPM has a negative and meaningful effect on stock prices, and inflation has an insignificant effect on stock prices. This study contributes to a better understanding of the factors influencing stock prices in the digital banking sector. The findings provide insights that can help investors, analysts, and policymakers make more informed decisions related to stock valuation and investment strategies in the context of Indonesia's growing digital banking industry.